Modernisasi (Studi pada Aktor Pertanian lahan basah Desa Samuda) - Ruswinarsih, Sigit; P, Reski (Jurnal Ilmiah Mandala Education (JIME), 2021)
Modernization appears in various forms, both in tangible and unconscious forms. Modernization has gripped all sectors of human life without exception even in private spaces to public spaces, starting from technological modernization to modernization at the level of ideas.The aim is to find out the actions of farmers in Samuda village in responding to modernization in agriculture and constraints. This study used qualitative research methods. The technique for determining the informants used in this study was a purposive technique, which means that the researcher determines the informants based on qualifications that are in accordance with the research topic. Data collection techniques were carried out by observation, interviews, and documentation. The results showed that the actions of farmers in responding to modernization with the use of modern elements in agriculture. This modern element varies from one farmer to another, from one farmer group to another, from one land type to another. In tidal swamp farming, it is not possible to apply all the elements of agricultural renewal, but there are several factors such as land type, water conditions and weather that need to be considered before starting the farming process. Samuda farmers use a combination of agricultural tools in land management. At the stage of land cultivation, they use tractors if land conditions allow. In this case if the state of water is little and the soil is dry or little water. This consideration is important because tidal swamps are highly dependent on the high and low water conditions with land that is always flooded. During the dry season, the water discharge is low, so farmers can use tractors to cultivate the land.Based on the results of the research above, it is recommended that the government be more intensive in providing understanding and training for farmers regarding the use of modern tools in farming activities.